Study on Flow Mechanism of a Morphing Supercritical Airfoil - Yuanjing Wang; Binbin Lv; Pengxuan Lei; Wenkui Shi; Yu Yan (Shock and Vibration)
In order to maintain the best performance in flight, a new concept, morphing aircraft, has been proposed, which can change the real-time aerodynamic characteristics under different flight conditions. The key problem is to figure out the response of strong flow instability caused by structure changes during the morphing. To solve this problem, computational fluid dynamics (CFD) and wind tunnel tests (WTT) were employed. The results show that the deformation of thickness and camber angle of the airfoil will significantly change the distribution of pressure and result in obvious hysteresis loops of lift and drag. With the increase of deformation frequency and amplitude, the instability increases correspondingly. Moreover, the unsteady effect caused by camber deformation is much stronger than that caused by thickness deformation. In addition, the flow structures on the airfoil, such as the shock strength and boundary separation location, have a delay in response to structure changes. Therefore, there will be a hysteresis between airfoil deformation and aerodynamic characteristics, which means strong flow instability.